Estudio de prefactibilidad para la instalación de una planta productora de geocontenedores a base de geotextil tejido - Cáceres Pérez, Yessenia Lisbeth (2020)
The present investigation shows us the production of an industrial polymer product of three-dimensional structure. The same that performs the functions of filtering, drainage, separation and as a barrier of impermeability. These aspects will be seen in depth in the first chapter. For the development of chapter two, the Estimation of Residual Water in Metropolitan Lima was taken as a basis. Administered by the Potable Water and Sewerage System of Lima - SEDAPAL. Which, provides information collected from the demand for services by each district. All this process is regulated by the National Superintendence of Sanitation Services - SUNASS. As for, chapter three was worked on based on different factors and location alternatives for the production plant. These parameters were evaluated trough of a macro and micro localization analysis through of a confrontation matrix. The plant size, chapter four, was determined by the market size relation. Because, it defines the production capacity with that the will work it is throughout the life of the project. In chapter 5, all technical part of the project is presented from the production of the product to the final sale service. It includes all necessary requirements, both tangible and intangible, and ends with an execution plan. For chapter 6; an administrative analysis was carried out, which helped us determine the organizational structure of the company. In relation to chapters 7 and 8, the feasibility (profitability) of the project was determined for a certain time of useful life. For this, a financial and economic evaluation was carried out. In addition, of a sensitivity analysis. To finish the investigation; we carried out a social analysis with regard to the positive impact that would be generated with the implementation of the production plant in the District of Lurín.